The Johannes a Lasco Library Emden – on the Way to a Self- supporting Library - Schulz, Walter (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The focus of this conference is new library architecture, so in my short lecture I will describe our new building and explain how it works. But to understand the special situation of the Emden library it is quite important to know the special and that means too the historical backround and to see the different ways we use the library - really uncommon for a church-library. Most of the libraries represented at this conference are university or state libraries. The Emden library project is not comparable to most of them. The Johannes a Lasco Library was for centuries the book collection only of the reformed communitiy at Emden and just the last ten years we started to build up a compehensive special-library in the field of reformed protestantism on the basis of this old collection, not a particularly large but a well sorted specified one. Today the library is organized as a foundation or registered charity according to German law and belongs to the Reformed Church of Germany.